EMOTIONAL INTELLIGENCE AND CREATIVITY IN KINSHASA'S SECONDARY SCHOOLS - Jonathan ENGUTA MWENZI; Eustache BANZA NSOMWE -ANFUNKWA; Léon MBADU KHONDE (Universitaria Publishing House, Craiova, 2023)
The aim of this study was to establish the relationship between emotional intelligence and creativity in students at a number of secondary schools in the city of Kinshasa. Two instruments (riddle test and emotional intelligence rating scale) were administered to a non-probabilistic sample of 137 secondary school pupils from two Kinshasa schools (Groupe Scolaire du Mont-Amba and Institut Pédagogique et Technique Mokengeli). The results attested to the existence of strong emotional intellectual potential. On the other hand, the creative level of the subjects surveyed was low. Regression analysis confirmed the positive effect of emotional intelligence on the creativity of the students targeted in the study.